Hybrid composites with epoxy resin matrix manufactured with vacuum casting technology - Oleksy, M.; Heneczkowski, M.; Oliwa, R.; Budzik, G.; Dziubek, T.; Markowska, O.; Szwarc-Rzepka, K.; Jesionowski, T. (Polimery, 2014)
The paper presents the methodology of the process of manufacturing of technical profile models on the example gear wheels made of epoxy composites cast in silicone molds using vacuum casting technology. Research on preparation of epoxy resin composites filled with hybrid modifiers has been carried out. Mechanical and processing properties of composites have been evaluated, particularly in terms of application in rapid prototyping of gear wheels. Considerable improvement of tensile strength (up to 44 %) and unnotched impact strength (up to 93 %) has been observed. Geometric accuracy of gear wheels prepared by casting of the analyzed hybrid composites has been determined using a coordinate measuring machine. Morphology of the brittle fracture of studied composites has been observed on brittle fractures using a scanning electron microscope (SEM).